An Ethnography of Taiwanese International Students’ Identity Movements: Habitus Modification and Improvisation - Hsieh, Jasper Kun-Ting (Journal of International Students, 2020)
Many studies focus on Chinese-speaking international students’ adaptation issues inside and outside educational settings in the West. A strong emphasis has been placed on identifying Chinese-speaking international students’ problems and solving them through educational programs, pedagogies, and curricula. This emphasis categorizes these students as a cohort that have issues learning and living in Western societies, a categorization that ignores identity as complex and context-dependent. Drawing on a Bourdieuian poststructuralist perspective, this 18-month-long study documented the experiences of nine Taiwanese international students at different Australian universities before, during, and after their 1-year postgraduate education in Australia. This study compared their experiences and highlighted the complexity of identity movements. The findings present habitus modification and habitus improvisation, two notions developed from a Bourdieuian perspective. In conclusion, this study encourages reassessment of the standard notions of adaptation and prompts further exploration of how international students use their overseas experiences in the home context.